Cutaneous ectopia of lung, located on back and neck: Hitherto undescribed presentation. (17th October 2021) - Osama, Md; Sharma, Rupali; Dhawan, Shashi
Abstract: Ectopia is defined as the presence of a normal‐appearing tissue in an abnormal location, where it is not normally found. In the literature, it is also referred to as heterotopia and is described as choristoma when it forms a mass. Lung tissue ectopia is a rare anomaly and is characterized by the presence of mature lung tissue comprising well‐formed bronchi, bronchioles, and alveoli at an abnormal location. Occurrence of ectopic lung tissue in the skin is an extremely rare entity and the diagnosis is mostly established by histopathologic examination. This report documents a rare occurrence of cutaneous ectopic lung tissue at two locations (neck and back). Cutaneous ectopia at multiple sites has not been described in the literature till date.